Getting traceability right, from fish to advanced bio-technological products: a review of legislation. (1st October 2015) - Borit, Melania; Santos, Jorge
Abstract: Traceability is a tool used by regulators to manage risk in multiple supply chains, including supply chains of goods derived from genetically modified organisms, human blood, seafood products, toys and hazardous waste. This tool may help support a variety of claims that range from concern for nature to consumer satisfaction and health. This paper examines the consistency of European Union legislation with the declared objective of the law, i.e., to implement a traceability system through the entire supply chain. This analysis is undertaken by benchmarking 30 European Union laws that introduced traceability in the supply chain of 16 groups of products. The conclusion is that one-half of these norms lack basic effective principles of traceability. The approaches implemented were strongly correlated with the original driver for risk management (for example, concern for environmental sustainability), moderately correlated with the type of goods involved and uncorrelated with their trade value. The paper forecasts traceability approaches for new products, and indicates how traceability systems can become operative, regardless of product and driver. In addition, the importance that the legal provisions are consistent with the declared objective of the law is discussed. This integrated view is useful for regulators, industry and consumers in general and provides legislators and businesses with guidelines for consistent application of traceability, which facilitates other processes, such as life cycle analysis. Concurrently, it provides the public with an understanding of what lies behind the (often) inaccessible wording of legal norms. Highlights: EU traceability laws applicable to 16 major groups of products were benchmarked. This study found that half of the norms lack basic effective traceability principles. Legislation is strict with respect to human health issues. Laws are laxer when environmental or other issues are at stake. Suggestions to harmonise legislation, regardless of traceability drivers, are made.